Utilidad y objetividad en la investigación científica - Valor Yébenes, Juan Antonio (Revista de Filosofía, 2007)
I think that the ideas of “an objective conception of reality” and of “a scientific method” are neither clear nor useful. In this paper I want to say why I think that, and to recommend a Deweyan approach to science, one which emphasizes the utility rather than the objectivity of laws and theories.